Praktik Etika Dalam Akuntansi Keuangan: Studi Kasus Pada Perusahaan AISA Group - Mutiara Aryanti Nur Cahyani; Rachmalyta Afifah Putri; Indah Aulia; Yesi Anidya Putri; Saridawati Saridawati (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to study the theory of ethics in financial accounting practices. Qualitative data is used to investigate ethical violations in financial accounting practices that occur in the AISA group when presenting its financial statements. The results show that the AISA group has committed ethical violations in financial accounting practices when providing its financial statements